Artificial Intelligence as A Driver of Digital Government Transformation: Applications and Trends in Government Operations in the Philippines - P. Pareja, Harold (Policy & Governance Review, 2025)
Digital transformation in government operations hastens transparency, efficiency, and customer satisfaction, and the application of artificial intelligence (AI) and machine learning (ML) can optimize digitalization initiatives. This study sought to identify the digitalization and digital transformation policies of the Philippine government and explore how AI technologies can be leveraged in government operations, specifically in frontline services, human resource management, and financial services. Document reviews are the primary methods. It examined legal government documents, published journal articles, and papers. Digital government transformation is still in its foundational/ initiation phase. However, it is noticeable that national policies on AI strategy are set, political support is evident, and government agencies are already leading the digitalization of their services. As AI adoption in digital government transformation has gained traction, there is a need to utilize AI technologies and algorithms to accelerate these efforts, thereby spurring economic growth. Potential AI technologies applicable to these identified services include predictive analytics, deep learning, neural networks, RNN, CNN, and recommender systems, among others.